SHARĪʿAH-COMPLIANT FINTECH USAGE AMONG MICROENTREPRENEURS IN MALAYSIA: AN EXTENSION OF UTAUT MODEL - Nik Hadiyan Nik Azman; Mohd Zaidi Md Zabri (Journal of Islamic Monetary Economics and Finance, 2022)
Fintech has been beneficial to the financial services industry and has markedly enhanced financial inclusivity. While the fintech has already made its mark, there has been somewhat limited use of sharīʿah-compliant fintech (such as P2P lending, crowdfunding, wealthtech, e-wallets) by Muslim microentrepreneurs (MEs) in Malaysia. Hence, this study examines the factors that affect sharīʿah-compliant fintech usage and its effect on income sustainability via an extended Unified Theory of Acceptance and Use of Technology (UTAUT). One hundred sixty-five (165) questionnaires were distributed to Muslim MEs who are users of sharīʿah-compliant fintech. This study reveals that performance expectancy and facilitating conditions have positive and significant effects on the use of sharīʿah-compliant fintech. The extended relationship of sharīʿah-compliant fintech adoption and income sustainability also presents a significant and positive relationship in which sharīʿah-compliant fintech has the potential to increase and, more importantly, sustain MEs’ income level.